Transalpinecine and Analogues: First Total Synthesis, Stereochemical Revision and Biological Evaluation. Issue 8 (30th January 2019) - Dehoux, Cécile; Castellan, Tessa; Enel, Morgane; André‐Barrès, Christiane; Mirval, Sandra; Becq, Frédéric; Ballereau, Stéphanie; Génisson, Yves
Abstract : The first total synthesis of transalpinecine, a pyrrolizidine alkaloid extracted from Heliotropium transalpinum is reported. The concise synthetic route developed towards these unusual iminosugar‐like natural compounds relies on an intramolecular Morita–Baylis–Hillman reaction. The four diastereoisomers of transalpinecine, as well as the two diastereoisomers of the parent epoxide subulacine, were prepared. 1 H NMR‐based stereochemical assignment of these different diastereoisomers was substantiated by quantum calculations of NMR shifts and coupling constants, allowing revision of the initially reported transalpinecine structure. One of these synthetic compounds significantly potentiates the activity of the F508del‐CFTR corrector VX‐809. Abstract : The first total synthesis of transalpinecine is reported. The four diastereoisomers of transalpinecine as well as the two diastereoisomers of the parent epoxide subulacine were prepared, allowing revision of the initially reported transalpinecine stereochemistry. One of these synthetic compounds significantly potentiates the activity of the F508del‐CFTR corrector VX‐809.